Genetic Evaluation Of Red Chittagong Cattle In Bangladesh (SAARC Journal of Agriculture, 2020)
The current study was carried out using data of the Nucleus Herd and Community Herd of Red Chittagong Cattle (RCC) established through USDA funded Red Chittagong Cattle project under the Department of Animal Breeding and Genetics, BAU, Mymensingh. Data on 151 calves and 75 lactating cows were analyzed. The estimated heritability values were 0.45 ± 0.05 for birth weight, 0.48 ± 0.05 for weaning weight, 0.41 ± 0.08 for pre-weaning daily gain, 0.47 ± 0.06 for lactation length, 0.43 ± 0.07 for lactation milk yield and 0.35 ± 0.09 for average daily milk yield. The highest Breeding Value (BV) were for birth weight (3.2 kg), weaning weight (24.46 kg), pre-weaning daily gain (82.39g), lactation length (52.25 days), lactation milk yield (186.04 kg) and average daily milk yield (0.66 kg). The minimum and maximum phenotypic index values by using phenotypic parameters were for growth traits (1196.24 and 4713.24) and milk production traits (8573.93 and 40670.81). The minimum and maximum genetic index values by using breeding values were for growth traits (1812.49 and 2870.21) and milk production traits (-1812.49 and 2870.21). All the estimated index values can be used in animal selection and breeding programs for RCC improvement and similar index selection can be applied for other indigenous cattle development programs in Bangladesh or elsewhere.SAARC J. Agri., 17(2): 141-154(2019)